The Marmara earthquake: admission laboratory features of patients with nephrological problems - (:unkn) unknown (OXFORD UNIV PRESS, 2002)
Background. Earthquakes are major causes of morbidity and mortality. North-western Turkey was struck by a devastating earthquake in August 1999, which caused several thousand deaths. Among the most important morbid events in survivors were acute nephrological problems. Methods. Within the first week of the disaster, specific questionnaires asking about 63 clinical and laboratory Parameters were sent to 35 reference hospitals that were treating the victims. Of the registered 639 victims, 423 were admitted within the first 3 days of the disaster, the admission laboratory data of these 423 patients are the subject of this analysis. Results. In the 423 patients (233 males, mean age 31.3+/-14.4 years), time under the rubble was 10.7+/-10.4 h. Mean values at admission were as follows: serum potassium 5.4+/-1.3 mEq/l, creatine phosphokinase 58 205+/-77 889 IU/l, albumin 2.6+/-0.7 g/dl, phosphorus 5.2+/-1.8 mg/dl, haematocrit 35.0+/-9.3%, 3 leukocyte count 14 945+/-6614/mm(3), platelet count 183 975+/-134 012/mm(3), blood urea nitrogen 55.1 +/- 28.9 mg/dl, and creatinine 3.9 +/- 2.3 mg/dl. Serum potassium above 6.5 mEq/l was noted in 91 patients (22.7%), an alarming finding for risk of fatal arrhythmias. Non-survivors were characterized by higher figures of serum potassium (P=0.001), as well as lower haematocrit (P=0.028), platelets (P<0.001), and serum albumin (P=0.003). In a multivariate analysis model of admission laboratory parameters, serum creatinine (P<0.001, o.r.=2.19), potassium (P=0.001, o.r.=3.64), and phosphorus (P=0.004, o.r.=1.78) predicted dialysis needs, whereas serum albumin (P=0.028, o.r.=0.23) and creatinine (P=0.039, o.r.=0.60) were related to mortality. Conclusions. Admission laboratory data may be useful for predicting dialysis needs and survival chance of disaster victims. High incidences of some life-threatening abnon-nalities dictate the need for empirical therapy even in the field.
Keywords: acute renal failure; crush syndrome; dialysis; hyperkalaemia; laboratory findings; Marmara earthquake; ACUTE-RENAL-FAILURE; HANSHIN-AWAJI EARTHQUAKE; RHABDOMYOLYSIS; MANAGEMENT; MORTALITY; VICTIMS